FAKTOR SEGMENTASI YANG MEMPENGARUHI KONSUMEN DALAM MENGGUNAKAN KARTU PROVIDER TELKOMSEL (STUDI KASUS PT. TELKOMSEL PEKANBARU) - Sania Ovila; Annisa Mardatillah (UIR Press, 2015)
The research was conducted at PT. Telkomsel Pekanbaru. PT Telkomsel is a companyengaged in the field of telecommunications. This company legalized on 26 May 1995 bydecision of the Minister of Tourism, Post and Telecommunications, as well as theFinance Minister as one of the GSM operators in Indonesia. In its development until2014 PT Telkomsel Being Users Most in Indonesia. Sence PT Telkomsel DoingSegmentation At consumers to be able to create products that comply with the wishesand needs of different customers. Factors Segmentation consists of Geographic,Demographic, Psychographic, and Behavior. The research goal is to analyze anddetermine the factors that influence consumer segmentation using Telkomsel card. Inthis study the authors used the data types and sources of primary data and secondarydata. Primary data is data obtained directly from the object of study which includesdata on the number's population, questionnaire data, data from interviews and otherdata deemed necessary. Secondary data is data obtained directly from the companywhere the research is PT Telkomsel Pekanbaru that his nature to support the analysis inthis study as a general overview of the company, as well as the number of usersTelkomsel card. And using two sampling techniques are accidental sampling for thewithdrawal of 50 consumers and purposive sampling to 10 Customer Service. Theresults of the four indicators is Good Enough, All this indicates that TelkomselProviders Card must be improved for the future.